Experimentally validated constitutive model for NiTi-based shape memory alloys featuring intermediate R-phase transformation: A case study of Ni48Ti49Fe3. (May 2021) - Frost, M.; Jury, A.; Heller, L.; Sedlák, P.
Abstract: An important group of NiTi-based alloys employed in applications exhibits an intermediate R-phase transformation, which substantially modifies the material's thermomechanical response. Finite element analysis of products from such alloys requires a constitutive model covering the two-stage transformation sequence in its full thermodynamic nature. We propose an enhanced constitutive model for NiTi-based alloys, which incorporates R-phase as a distinctive phase with loading-dependent transformation strain. We validate the model on a newly acquired extensive experimental dataset on the thermomechanical response of Ni48 Ti49 Fe3 shape memory alloy and illustrate the capabilities of its implementation into finite element software on a computational structural analysis of a tightening ring. Graphical abstract: Unlabelled Image Highlights: An enhanced constitutive model for NiTi-based alloys incorporating R-phase is proposed. The model is validated using an experimental dataset on the thermomechanical response of Ni48 Ti49 Fe3 shape memory alloy. The algorithmic implementation into finite element software is tested on a computational analysis of a tightening ring.